Secure Grayscale Image Encryption Using DNA-Based Randomized Sequencing Technique and Pseudorandom Number Generation - Dhakal, Madhav; Yadav, Hari Narayan Ray (Journal of Engineering Issues and Solutions, 2026)
In this research, a random selection technique for sequencing DNA bases with a secret key encryption technique is proposed. Two layers of encryption techniques are proposed in this research. Here, the first layer is inspired by the Feistel structure which includes the mathematical logical operation, including the XOR operation. In this layer, the security of image date is maintained by the Pseudo Random Number Generation (PRNG) and the second layer is followed by the concept of the biological information transform process.In this proposed technique, the generation of the permutation box depends upon the inputted image, which creates more randomness and makes it difficult to guess the secret key and maintain confidentiality from the intruder. Here, the seed value works as the private key. In this encryption technique, first, the original image is divided into various blocks of 256 bit size and padding is necessary if the last block does not contain the bits of 256 size and then data obtained from the blocks are XOR with the key value. After that, results obtained from this operation are transformed into the cipher image using the concept of DNA cryptography translation.